Transporters as mediators of drug resistance in Plasmodium falciparum - Sanchez, Cecilia P.; Dave, Anurag; Stein, Wilfred D.; Lanzer, Michael (International journal for parasitology, 2010)
Drug resistance represents a major obstacle in the radical control of malaria. Drug resistance can arise in many different ways, but recent developments highlight the importance of mutations in transporter molecules as being major contributors to drug resistance in the human malaria parasite Plasmodium falciparum. While approximately 2.5% of the P. falciparum genome encodes membrane transporters, this review concentrates on three transporters, namely the chloroquine resistance transporter PfCRT, the multi-drug resistance transporter 1 PfMDR1, and the multi-drug resistance-associated protein PfMRP, which have been strongly associated with resistance to the major antimalarial drugs. The studies that identified these entities as contributors to resistance, and the possible molecular mechanisms that can bring about this phenotype, are discussed. A deep understanding of the underpinning mechanisms, and of the structural specificities of the players themselves, is a necessary basis for the development of the new drugs that will be needed for the future armamentarium against malaria.